Upper Leg Muscular Co-Contraction During Maximal-Speed Sprinting in Male Club Ice Hockey Athletes - Jason J. Williams; William C. Roshinski; Joseph C. Watso (Sports Medicine - Open)
Abstract Background Little is known about the lower extremity muscle co-contraction patterns during sprinting and its relation to running velocity (i.e., performance). Therefore, we compared lower extremity muscular activation patterns during sprinting between slower and faster collegiate club hockey athletes. We hypothesized that faster athletes would have lower EMG-assessed co-contraction index (CCI) values in the lower extremities during over-ground sprinting. Methods Twenty-two males (age = 21 [1] yrs (median[IQR]); body mass = 77.1 ± 8.6 kg (mean ± SD)) completed two 20-m over-ground sprints with concomitant EMG and asynchronous force plate testing over four days in Tallahassee, Florida, USA. We split participants using median running velocity (FAST: 8.5 ± 0.3 vs. SLOW: 7.7 ± 0.3 m/s, p < 0.001). Results Faster athletes had lower CCI between the rectus femoris and biceps femoris (group: p = 0.05), particularly during the late swing phase of the gait cycle (post hoc p = 0.02). Early swing phase duration was moderately inversely related to Hip CCI in the stance phase (ρ=-0.58, p < 0.01) and weakly related to Knee CCI in the swing phase (ρ = 0.44, p = 0.046). Finally, swing phase duration was moderately inversely related to Hip CCI in the stance phase (ρ=-0.50, p = 0.02). Conclusions In agreement with our hypothesis, we found lower CCI values in the upper leg musculature during maximal-speed over-ground sprinting. These data from collegiate club hockey athletes corroborate other reports in clinical populations that the coordination between the rectus femoris and biceps femoris is associated with linear over-ground sprinting velocity.